Managerial workarounds in three European DRG systems. Issue 3 (14th February 2020) - Sheaff, Rod; Morando, Verdiana; Chambers, Naomi; Exworthy, Mark; Mahon, Ann; Byng, Richard; Mannion, Russell
Abstract : Purpose: Attempts to transform health systems have in many countries involved starting to pay healthcare providers through a DRG system, but that has involved managerial workarounds. Managerial workarounds have seldom been analysed. This paper does so by extending and modifying existing knowledge of the causes and character of clinical and IT workarounds, to produce a conceptualisation of the managerial workaround. It further develops and revises this conceptualisation by comparing the practical management, at both provider and purchaser levels, of hospital DRG payment systems in England, Germany and Italy. Design/methodology/approach: We make a qualitative test of our initial assumptions about the antecedents, character and consequences of managerial workarounds by comparing them with a systematic comparison of case studies of the DRG hospital payment systems in England, Germany and Italy. The data collection through key informant interviews ( N  = 154), analysis of policy documents ( N  = 111) and an action learning set, began in 2010–12, with additional data collection from key informants and administrative documents continuing in 2018–19 to supplement and update our findings. Findings: Managers in all three countries developed very similar workarounds to contain healthcare costs to payers. To weaken DRG incentives to increase hospital activity, managers agreed to lower DRG payments for episodes of care above an agreed case-load 'ceiling' and reduced payments by less than the full DRG amounts when activity fell below an agreed 'floor' volume. Research limitations/implications: Empirically this study is limited to three OECD health systems, but since our findings come from both Bismarckian (social-insurance) and Beveridge (tax-financed) systems, they are likely to be more widely applicable. In many countries, DRGs coexist with non-DRG or pre-DRG systems, so these findings may also reflect a specific, perhaps transient, stage in DRG-system development. Probably there are also other kinds of managerial workaround, yet to be researched. Doing so would doubtlessly refine and nuance the conceptualisation of the 'managerial workaround' still further. Practical implications: In the case of DRGs, the managerial workarounds were instances of 'constructive deviance' which enabled payers to reduce the adverse financial consequences, for them, arising from DRG incentives. The understanding of apparent failures or part-failures to transform a health system can be made more nuanced, balanced and diagnostic by using the concept of the 'managerial workaround'. Social implications: Managerial workarounds also appear outside the health sector, so the present analysis of managerial workarounds may also have application to understanding attempts to transform such sectors as education, social care and environmental protection. Originality/value: So far as we are aware, no other study presents and tests the concept of a 'managerial workaround'. Pervasive, non-trivial managerial workarounds may be symptoms of mismatched policy objectives, or that existing health system structures cannot realise current policy objectives; but the workarounds themselves may also contain solutions to these problems.